2016
DOI: 10.1007/s10554-016-0854-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of sub-mSv prospective ECG-triggering cardiac CT in young infant with complex congenital heart disease

Abstract: To explore the clinical value and evaluate the diagnostic accuracy of sub-mSv low-dose prospective ECG-triggering cardiac CT (CCT) in young infants with complex congenital heart disease (CHD). A total of 102 consecutive infant patients (53 boys and 49 girls with mean age of 2.9 ± 2.4 m and weight less than 5 kg) with complex CHD were prospectively enrolled. Scans were performed on a 64-slice high definition CT scanner with low dose prospective ECG-triggering mode and reconstructed with 80 % adaptive statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Third, although retrospectively ECG-triggered MDCTA more clearly depicts ventricular morphology than helical CT scanning mode, retrospective ECG-gating is currently not recommended as a routine MDCTA protocol because of its higher radiation dose compared with helical scanning mode. Recent studies showed that the use of prospective ECG-gating significantly reduces the radiation exposure to patients undergoing MDCTA and yields diagnostic image quality in the assessment of coronary arteries [ 42 45 ], coronary artery bypasses [ 46 ], and congenital heart disease [ 47 ] with lower radiation dose. Future studies are warranted that evaluate the diagnostic accuracy of low-dose prospectively ECG-triggered MDCTA in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although retrospectively ECG-triggered MDCTA more clearly depicts ventricular morphology than helical CT scanning mode, retrospective ECG-gating is currently not recommended as a routine MDCTA protocol because of its higher radiation dose compared with helical scanning mode. Recent studies showed that the use of prospective ECG-gating significantly reduces the radiation exposure to patients undergoing MDCTA and yields diagnostic image quality in the assessment of coronary arteries [ 42 45 ], coronary artery bypasses [ 46 ], and congenital heart disease [ 47 ] with lower radiation dose. Future studies are warranted that evaluate the diagnostic accuracy of low-dose prospectively ECG-triggered MDCTA in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…The scan parameters for prospective scanning were the same as that of our previous study. 8 The detailed parameters were as follows: prospectively ECGtriggered step-and-shoot axial scanning and a collimation of 64 3 0.625 mm with a scan field of view of 25 cm and gantry rotation time of 0.35 s. The data acquisition window was 380 ms with padding technique. The centre of the data acquisition window was set at 35-45% of the R-R interval when heart rate was over 75 bpm and at 65-85% of the R-R interval when heart rate was lower than 75 bpm.…”
Section: Methods and Materials Study Groups And Ct Scanningmentioning
confidence: 99%
“…Since then, innovations such as prospective ECG gating, ECG-controlled tube current modulation, high-pitch helical scanning, lower tube potentials, wider detector coverage, and iterative reconstruction techniques have dramatically lowered radiation exposure [33,34]. Today, sub-milliSievert scans are achievable in many children [35]. However, effective doses still vary widely, and recently published pediatric cardiac-specific dose-length product conversion or "k-"factors suggest that k-factors, and therefore effective cardiac radiation doses, in children are considerably higher than previously believed [32,36].…”
Section: Benefits Of Cardiovascular Ct In Cyanotic Chdmentioning
confidence: 99%
“…With dual-source scan technology and wide detector coverage, studies can be obtained in a single heartbeat without requiring a breath hold for most indications. General anesthesia and paralysis are not necessary in most patients [35,36]. While cardiac MRI in critically ill and often unstable patients poses significant risks because of study length, need for sedation, the need to change MRI-incompatible ventilators and lines, and difficulties with closely monitoring patients inside the scanner, cardiac CT mitigates these risks.…”
Section: Benefits Of Cardiovascular Ct In Cyanotic Chdmentioning
confidence: 99%